2021
DOI: 10.1016/j.cell.2021.02.044
|View full text |Cite
|
Sign up to set email alerts
|

A trans-complementation system for SARS-CoV-2 recapitulates authentic viral replication without virulence

Abstract: The biosafety level-3 (BSL-3) requirement to culture severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a bottleneck for research. Here we report a trans -complementation system that produces single-round infectious SARS-CoV-2 that recapitulates authentic viral replication. We demonstrate that the single-round infectious SARS-CoV-2 can be used at BSL-2 laboratories for high-throughput neutralization and antiviral testing. The trans -complementation sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 48 publications
1
83
0
Order By: Relevance
“…For cell-based antiviral testing, both wild-type virus and those engineered to express reporter genes like luciferase or fluorescent proteins have been used to screen compounds for antiviral activity [ 70 , 71 ]. A single-round infectious SARS-CoV-2 that recapitulates authentic virus infection and replication without virulence has recently been developed to facilitate antiviral screening at BSL-2 [ 72 ]. Antiviral activity and potency have been determined by multiple techniques, including through the measurement of reporter gene products, direct measure of infectious virus by classical virologic techniques, measurement of viral cytopathic effect in cell monolayers, and immunostaining-based measurement of viral proteins via high-content imaging, which can also monitor cytotoxicity [ 59 ].…”
Section: Preclinical Toolsmentioning
confidence: 99%
“…For cell-based antiviral testing, both wild-type virus and those engineered to express reporter genes like luciferase or fluorescent proteins have been used to screen compounds for antiviral activity [ 70 , 71 ]. A single-round infectious SARS-CoV-2 that recapitulates authentic virus infection and replication without virulence has recently been developed to facilitate antiviral screening at BSL-2 [ 72 ]. Antiviral activity and potency have been determined by multiple techniques, including through the measurement of reporter gene products, direct measure of infectious virus by classical virologic techniques, measurement of viral cytopathic effect in cell monolayers, and immunostaining-based measurement of viral proteins via high-content imaging, which can also monitor cytotoxicity [ 59 ].…”
Section: Preclinical Toolsmentioning
confidence: 99%
“…Reverse genetics systems for SARS-CoV-2, the causative agent of COVID-19, have been developed for fully-infectious recombinant virus production (10)(11)(12)(13) and as replicon platforms (14)(15)(16)(17)(18)(19). In the latter case, trans-complementation of the deleted structural gene nucleocapsid (N) (18) or envelope (E) and Orf3a genes (19) can enable single-cycle infectious SARS-CoV-2 virion production that may reduce the need for high containment for a range of applications. While these systems permit spike-dependent replicon delivery, interrogating newly emerging spike variants requires replicon reengineering for each variant.…”
mentioning
confidence: 99%
“…The structural envelope (E) protein shares striking functional similarities in different coronaviruses, including SARS-CoV, MERS-CoV [ 52 ]. In addition to the essential roles of 2-E channel we identified, it has been found that deletion of E channel results in attenuating SARS-CoV pathogenesis [ 53 55 ]. Beyond that, E channel was also found to participate in MERS-CoV assembling, virion release, and pathogenesis [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%